An Integrated Design with new Metal‐Functionalized Covalent Organic Frameworks for the Effective Electroreduction of CO2 - Yao, Cang‐Lang; Li, Jian‐Chen; Gao, Wang; Jiang, Qing (Chemistry : a European journal, 2018)
One of the long‐standing issues that prohibits large‐scale CO2 reutilization is the low aqueous solubility of CO2 and the incurring inefficient mass transport of CO2. Herein, we suggest a feasible way to promote the CO2 reutilization by integrating the storage and reduction, with a new covalent organic framework (COF) series constituted by cobalt‐phthalocyanine and boronic acid linkers. We find that the porous structure of the cobalt COF is competitive in the CO2 storage and can sustain a high CO2 concentration around the reduction center, whereas the mass transport of CO2 as well as the efficiency of the CO2 reduction is significantly improved. The predicted cobalt COF exhibits an overpotential of 0.27 V and a CO production rate, which is 97.7 times higher than in aqueous solution, for the CO2 reduction. Our work provides a promising candidate for the CO2 reutilization, with valuable insights and an important prototype for future practical design. Synergistic effects: A new covalent organic framework (COF), which combines CO2 storage and reduction sites in one place (see figure), sustains a high local concentration of CO2, which remarkably promotes the reduction efficiency.